Implementation of Digital-Based Authentic Assessment to Assess Observing, Inferring and Predicting Skills in Prospective Chemistry Teachers - Isna Rezkia Lukman; Ratna Unaida; Sri Setiawaty; Najiha Sabrina (Postgraduate, University of Mataram, 2023)
As the spearhead of successful learning in the classroom, a prospective teacher must have qualified abilities and skills, teacher competence and teaching quality need to be ensured. One of the ways to measure the competence of prospective chemistry teachers is by using authentic assessments. This assessment can be done digitally through an authentic digital-based assessment with a project-based learning model. The model, research design and instrument development carried out in this study is an adaptation of the test preparation procedure with the following instrument preparation steps: (1) planning the test, (2) trying out the test, (3) establishing test validity, (4) establishing test reliability, (5) interpreting the score. In this study, there were three parameters studied, namely (1) Analysis of the needs of prospective teachers at school. (2) Preparation of authentic assessment instruments that have been developed based on validators, (3) Analysis of observing, inferring and predicting skills. Analysis of school needs is the basis for the preparation of authentic assessment instruments and models that are compiled. The results of the learning instruments that have been compiled and have been developed have excellent quality criteria with an average per aspect of 0.875 and are declared valid based on the assessment of material experts, media experts and peer reviewers. The validated instrument is then implemented where the Implementation Analysis on prospective teachers in the observing aspect gets a score of 3,374 including in the excellent category, as for inferring, it gets a score of 3,217 including in the good category, in the predicting aspect it gets a score of 3,553 including the excellent category, so that the average teacher candidate gets a score of 3,392 including the excellent category. Meanwhile, the affective instrument of students got a score of 3.22 on the persistence aspect and 3.16 on the attention aspect, both of which were in the good category. So that the average affective aspect of the participants got a score of 3.19 and was included in the good category